2013
DOI: 10.4102/sajbm.v44i3.160
|View full text |Cite
|
Sign up to set email alerts
|

Relation between business satisfaction and board dimensions in joint ventures between Spanish and Moroccan SMEs

Abstract: Businesses commonly access new markets through joint ventures, and these partnerships may adopt diverse structures of government, among which the Board of Directors often plays a key role. Accordingly, the aim of this study is to observe which characteristics of the Board most affect the success of joint ventures between Spanish and Moroccan SMEs, operating in Morocco. Using a structured questionnaire, we analyse the characteristics of the Board that affect success, as measured by the partners' satisfaction wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 80 publications
(74 reference statements)
0
6
0
Order By: Relevance
“…Zaheer & Mosakowski, 1997) and facilitating the deployment of the relevant expertise and capabilities to create the stability needed for the success of the IJV has been discussed in the IJV literature. In the context of Africa, empirical evidence suggests the appointment of a CEO who hails from the host country of the IJV or a CEO who understands the local market has a positive influence on the performance of the IJV (Argente-Linares et al, 2013a, 2013bGómez-Miranda et al, 2015). While Choi and Beamish (2004) did not find any significant performance differences in local partner-dominant management, we saw a significant positive role played by local partners in the performance of IJVs in Africa (Bartels et al, 2002;Boateng & Glaister, 2003;Dadzie et al, 2014;Hearn, 2015;Luiz & Charalambous, 2009).…”
Section: Propositionsmentioning
confidence: 55%
See 4 more Smart Citations
“…Zaheer & Mosakowski, 1997) and facilitating the deployment of the relevant expertise and capabilities to create the stability needed for the success of the IJV has been discussed in the IJV literature. In the context of Africa, empirical evidence suggests the appointment of a CEO who hails from the host country of the IJV or a CEO who understands the local market has a positive influence on the performance of the IJV (Argente-Linares et al, 2013a, 2013bGómez-Miranda et al, 2015). While Choi and Beamish (2004) did not find any significant performance differences in local partner-dominant management, we saw a significant positive role played by local partners in the performance of IJVs in Africa (Bartels et al, 2002;Boateng & Glaister, 2003;Dadzie et al, 2014;Hearn, 2015;Luiz & Charalambous, 2009).…”
Section: Propositionsmentioning
confidence: 55%
“…Another study found a greater likelihood of a larger initial investment of capital in the case of IJVs with public companies than IJVs with private companies (Boateng et al, 2002). In a majority of cases, foreign CEOs and top officials were seen as a better management resource (Bartels et al, 2002); however, one case revealed that local CEOs had a positive effect on the performance of the IJV (Argente‐Linares et al, 2013a, 2013b). In addition, Banai and Akande (2005) found a difference in the case of South Africa, where the local managers preferred to hold a majority of the high managerial positions (compared to the foreign JV partners).…”
Section: What Do We Know About Ijv Research Themes In Africa?mentioning
confidence: 99%
See 3 more Smart Citations